VAC THERAPY IN THE TREATMENT OF PATIENTS WITH PHLEGMONS OF THE NECK, WITH DIABETES MELLITUS: // Collection of abstracts of the scientific and practical conference «Current Problems of Surgical Soft Tissue Infections» (2024), Tashkent, October 28 - Atakov, S.S.; Atajonov, T.Sh.; Yorkulov, A.Sh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The developed phlegmon in the neck is aggravated by the presence of concomitant diseases, in particular diabetes mellitus. A danger to the life of a patient with phlegmon of the neck is due to the anatomical and topographic features of this area, the rapid spread of the inflammatory process through the cellular spaces, and the development of mediastinitis and generalisation of the infection. Our study aimed to investigate VAC therapy's effectiveness in treating patients with phlegmon of the neck in diabetes mellitus.